Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-12+(x-9) < 0
=> -12+x-9 < 0
=> x - 21 < 0
=> x < 21
Vậy x < 21
Tk mk nha
a) 2 . x + 12 = 36
2 . x = 36 - 12
2 . x = 24
x = 24 : 2
x = 12
Vậy x = 12
b) (x + 21) : 8 + 12 = 21
( x + 21 ) : 8 = 21 - 12
( x + 21 ) : 8 = 9
x + 21 = 9 . 8
x + 21 = 72
x = 72 - 21
x = 51
Vậy x = 51
c) (3 . x - 18) . (x - 9) = 0
\(\Rightarrow\begin{cases}3.x-18=0\\x-9=0\end{cases}\)
\(\Rightarrow\begin{cases}3.x=18\\x=0+9\end{cases}\)
\(\Rightarrow\begin{cases}x=18:3=6\\x=9\end{cases}\)
Vậy \(x\in\left\{6;9\right\}\)
a)
\(2x+12=36\)
\(\Rightarrow2\left(x+6\right)=36\)
\(\Rightarrow x+6=18\)
=> x = 12
Vậy x = 12
b)
\(\left(x+21\right):8+12=21\)
\(\Rightarrow\left(x+21\right):8=9\)
\(\Rightarrow x+21=72\)
=> x = 51
Vậy x = 51
c)
\(\left(3x-18\right)\left(x-9\right)=0\)
\(\Rightarrow3\left(x-6\right)\left(x-9\right)=0\)
\(\Rightarrow\left(x-6\right)\left(x-9\right)=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}x-6=0\\x-9=0\end{array}\right.\)
\(\Rightarrow\left[\begin{array}{nghiempt}x=6\\x=9\end{array}\right.\)
Vậy x = 6 ; x = 9
Ta có :\(\frac{x+8}{12}+\frac{x+9}{11}+\frac{x+10}{10}+3=0\)
=> \(\left(\frac{x+8}{12}+1\right)+\left(\frac{x+9}{11}+1\right)+\left(\frac{x+10}{10}+1\right)=0\)
=> \(\frac{x+20}{12}+\frac{x+20}{11}+\frac{x+20}{10}=0\)
=> \(\left(x+20\right)\left(\frac{1}{12}+\frac{1}{11}+\frac{1}{10}\right)=0\)
Vì \(\frac{1}{12}+\frac{1}{11}+\frac{1}{10}\ne0\)
=> x + 20 = 0
=> x = -20
Vậy x = -20
\(\frac{x+8}{12}+\frac{x+9}{11}+\frac{x+10}{10}+3=0\)
\(\Leftrightarrow\left(\frac{x+8}{12}+1\right)+\left(\frac{x+9}{11}+1\right)+\left(\frac{x+10}{10}+1\right)=0\)
\(\Leftrightarrow\frac{x+20}{12}+\frac{x+20}{11}+\frac{x+20}{10}=0\)
\(\Leftrightarrow\left(x+20\right)\left(\frac{1}{12}+\frac{1}{11}+\frac{1}{10}\right)=0\)
Vì \(\frac{1}{12}+\frac{1}{11}+\frac{1}{10}\ne0\)
\(\Rightarrow x+20=0\Rightarrow x=-20\)
a) -12 + ( -9 + x ) = 0
( -9 + x ) = 0 + 12
( -9 + x ) = 12
x = 12 + 9
x = 21
Vậy x = 21
b) 21 + ( 25 - x ) = 2
( 25 - x ) = 2 - 21
( 25 - x ) = -19
x = 25 + 19
x = 44
Vậy x = 44
c) 461 + ( x - 45 ) = 387
( x - 45 ) = 387 - 461
( x - 45 ) = -74
x = - 74 + 45
x = -29
Vậy x = -29
a, => -12-9+x = 0
=> x-21 = 0
=> x=0+21 = 21
b, => 21+25-x = 2
=> 46-x = 2
=> x = 46-2 = 44
c, => 461+x-45 = 387
=> 416+x = 387
=> x = 387 - 416 = -29
Tk mk nha
a) -9 - 12 (x-5)+7(3-x)=15
<=> -9 - 12x + 60 + 21 - 7x = 15
<=> -12x - 7x = 15 + 9 - 60 - 21
<=> -19x = -57
<=> x = 3
Vậy ...
b ) x(x+2)>0
Ta xét 2 trường hợp :
TH1 : \(\hept{\begin{cases}x>0\\x+2>0\end{cases}}\Rightarrow\hept{\begin{cases}x>0\\x>-2\end{cases}}\Rightarrow x>0\)0
TH2 : \(\hept{\begin{cases}x< 0\\x+2< 0\end{cases}}\Rightarrow\hept{\begin{cases}x< 0\\x< -2\end{cases}}\Rightarrow x< -2\)
Vậy ...
c ) (x+1)(x+5)<0
Xét 2 trường hợp :
TH1 : \(\hept{\begin{cases}x+1< 0\\x+5>0\end{cases}}\Rightarrow\hept{\begin{cases}x< -1\\x>-5\end{cases}}\Rightarrow-5< x< -1\)
TH2 : \(\hept{\begin{cases}x+1>0\\x+5< 5\end{cases}}\Rightarrow\hept{\begin{cases}x>-1\\x< -5\end{cases}}=>x< -1vàx< -5\)
Vậy ...
a , -9 - 12x + 60 + 21 - 7x = 15
-19x + 72 = 15
-19x = -57
x = 3
\(\dfrac{x+8}{12}+\dfrac{x+9}{11}+\dfrac{x+10}{10}+3=0\\ \Leftrightarrow\dfrac{x+8}{12}+1+\dfrac{x+9}{11}+1+\dfrac{x+10}{10}+1=0\\ \Leftrightarrow\dfrac{x+20}{12}+\dfrac{x+20}{11}+\dfrac{x+20}{10}=0\\ \Leftrightarrow\left(x+20\right)\left(\dfrac{1}{12}+\dfrac{1}{11}+\dfrac{1}{10}\right)=0\\ \Leftrightarrow x+20=0\Leftrightarrow x=-20\\ KL:...\)
`<=>((x+8)/12+1)+((x+9)/11+1)+((x+10)/10+1)=0`
`<=>(x+20)/12+(x+20)/11+(x+20)/10=0`
`<=>(x+20)(1/12+1/11+1/10)=0`
Vì `1/12+1/11+1/10 ≠ 0`
`=>x+20=0`
`=>x=0-20`
`=>x=-20`
- 12 + ( x - 9)=0
x= 0 + 9 + 12
x= 21